Elizabeth's secret diary - William, Kate.; Pascal, Francine; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 1994)
Everyone thinks Elizabeth Wakefield is Miss perfect, but only her diary knows the truth.
"Francine Pascal's Sweet Valley high"--Cover.
Keywords: Diaries -- Fiction; Twins -- Fiction